Moisture Adsorption Isotherm Model for Edible Food Film Packaging – A Review / Aqila Zulaikha Nazreen …[et al.] - Nazreen, Aqila Zulaikha; Jai, Junaidah; Ali, Sherif Abdulbari; Mohamed Manshor, Norasmah (Universiti Teknologi MARA Shah Alam, 2020)
Bioplastic has been extensively studied due to its ability to replace synthetic plastics. Its biodegradability is seen as a significant advantage to be used as edible food film packaging. As a food packaging, the film should be able to retain moisture from the food and the surrounding environment. The ability of the film to retain moisture varies with the type of material the film is made of. Moisture sorption isotherms are used to study the moisture content and water activity of food or film packaging at a given temperature. There are many models to describe moisture sorption isotherm. Some researchers modified the models to account for varying temperatures. The purpose of this paper is to review types of adsorption isotherms and the most common models used for film packaging. The general and modified models are described in this paper as well as its best-fit use on film packaging. The advantages of studying adsorption isotherm include shelf-life determination, physical and chemical stability, and others.